GLOBAL SCIENTIFIC APPROACHES TO ENSURING ENVIRONMENTAL SUSTAINABILITY AND SECURITY: IMPLICATIONS FOR PRIMARY EDUCATION (Eureka Journal of Education & Learning Technologies, 2026)
The article analyzes the content of contemporary scientific issues related to ecological sustainability and environmental security, and highlights their impact on the primary education process. Methodological approaches, didactic opportunities, and pedagogical conditions for teaching global environmental issues, adapted to the age and psychological characteristics of young learners, are examined on a scientific basis. The importance of early development of environmental literacy for sustainable development is justified.
Keywords: ecological sustainability, environmental security, primary education, environmental literacy, environmental education, global environmental issues.